Effect of cannabis on oxaliplatin-induced peripheral neuropathy among oncology patients: a retrospective analysis. (February 2021) - Waissengrin, Barliz; Mirelman, Dan; Pelles, Sharon; Bukstein, Felix; Blumenthal, Deborah T.; Wolf, Ido; Geva, Ravit
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and dosage-limited oxaliplatin-related toxicity. To date, there are no successful interventions for CIPN prevention or treatment. A therapeutic role for cannabis in diabetic and HIV-related peripheral neuropathy and a protective role in CIPN have been suggested. We examined the effect of cannabis on oncologic patients with CIPN. Methods: Medical records of 768 consecutive patients treated with oxaliplatin and 5-fluorouracil-based combinations at a tertiary medical center from October 2015 to January 2018 were reviewed. Excluded patients were those with pre-existing neuropathy or patients who received fewer than two cycles of oxaliplatin treatment. CIPN grade, oxaliplatin cumulative dose, and neuropathy-free survival were evaluated. The patients were divided based upon the exposure to cannabis: prior to oxaliplatin (cannabis-first), cannabis following the initiation of oxaliplatin treatment (oxaliplatin-first), and no exposure (control). Results: In total, 513 patients met the inclusion criteria, of whom 248 were treated with cannabis and 265 served as controls. The cannabis-first group included 116 (46.7%) patients and the oxaliplatin-first group included 132 (53.3%) patients. Demographic parameters were comparable between groups. There was a significant difference in CIPN grade 2–3 between cannabis-exposed patients and controls (15.3% and 27.9%, respectively, p < 0.001). The protective effect of cannabis was more pronounced among cannabis-first patients compared to oxaliplatin-first patients (75% and 46.2%, respectively, p < 0.001). The median oxaliplatin cumulative doses were higher in the cannabis-first versus the oxaliplatin-first versus the control groups (545 mg/m 2, 340 mg/m 2, and 425 mg/m 2 respectively, p < 0.001). Conclusion: The rate of neuropathy was reduced among patients treated with cannabis and oxaliplatin. This reduction was more significant in patients who received cannabis prior to treatment with oxaliplatin, suggesting a protective effect. A large prospective trial is planned.